Distinctive Features of NREM Parasomnia Behaviors in Parkinson’s Disease and Multiple System Atrophy - Ratti, Pietro-Luca (PLoS One, 2015)
OBJECTIVE: To characterize parasomnia behaviors on arousal from NREM sleep in Parkinson’s Disease (PD) and Multiple System Atrophy (MSA). METHODS: From 30 patients with PD, Dementia with Lewy Bodies/Dementia associated with PD, or MSA undergoing nocturnal video-polysomnography for presumed dream enactment behavior, we were able to select 2 PD and 2 MSA patients featuring NREM Parasomnia Behviors (NPBs). We identified episodes during which the subjects seemed to enact dreams or presumed dream-like mentation (NPB arousals) versus episodes with physiological movements (no-NPB arousals). A time-frequency analysis (Morlet Wavelet Transform) of the scalp EEG signals around each NPB and no- NPB arousal onset was performed, and the amplitudes of the spectral frequencies were compared between NPB and no-NPB arousals. RESULTS: 19 NPBs were identified, 12 of which consisting of ‘elementary’ NPBs while 7 resembling confusional arousals. With quantitative EEG analysis, we found an amplitude reduction in the 5-6 Hz band 40 seconds before NPBs arousal as compared to no-NPB arousals at F4 and C4 derivations (p<0.01). CONCLUSIONS: Many PD and MSA patients feature various NREM sleep-related behaviors, with clinical and electrophysiological differences and similarities with arousal parasomnias in the general population. SIGNIFICANCE: This study help bring to attention an overlooked phenomenon in neurodegenerative diseases.